Homelessness in the Medical Curriculum: An Analysis of Case-Based Learning Content From One Canadian Medical School. Issue 1 (2nd January 2016) - To, Matthew J.; MacLeod, Anna; Hwang, Stephen W.
Abstract: Phenomenon : Homelessness is a major public health concern. Given that homeless individuals have high rates of mortality and morbidity, are more likely to be users of the healthcare system, and often report unmet health needs, it is important to examine how homelessness is addressed in medical education. We wanted to examine content and framing of issues related to homelessness in the case-based learning (CBL) curriculum and provide insights about whether medical students are being adequately trained to meet the health needs of homeless individuals through CBL. Approach : CBL content at a Canadian medical school that featured content related to homelessness was analyzed. Data were extracted from cases for the following variables: curriculum unit (e.g., professionalism/ethics curriculum or biomedical/clinical curriculum), patient characteristics (e.g., age, sex), and medical and social conditions. A thematic analysis was performed on cases related to homelessness. Discrepancies in analysis were resolved by consensus. Findings : Homelessness was mentioned in five (2.6%) of 191 CBL cases in the medical curriculum. Homelessness was significantly more likely to be featured in professionalism/ethics cases than in biomedical/clinical cases ( p = .03). Homeless patients were portrayed as socially disadvantaged individuals, and medical learners were prompted to discuss ethical issues related to homeless patients in cases. However, homeless individuals were largely voiceless in cases. Homelessness was associated with serious physical and mental health concerns, but students were rarely prompted to address these concerns. Insights : The health and social needs of homeless individuals are often overlooked in CBL cases in the medical curriculum. Moreover, stereotypes of homelessness may be reinforced through medical training. There are opportunities for growth in addressing the needs of homeless individuals through medical education.